Operational excellence in public administration: initial assessment - Rico, Cristina (Estado, Gobierno y Gestión Pública, 2019)
The object of the work that is exposed next has been to carry out the Initial Evaluation of the Management System of the Department of Administrative Procedures of the Government of Andorra. For this evaluation, the methodology described by Sonia Martín Pérez and Paulino Martin Seco has been followed in its “Guide for the implementation of process-based management in Public Administration”. With the model described, the authors intend to help public managers to lead their organizations to the operational excellence. As a result of the analysis carried the strengths and opportunities for improvement of the Management System of the Department of Procedures have been identified. The work presented is part of a broader proposal that covers the different stages that make up the process of continuous improvement, applied to Public Administration of European microstates.